Sources of Variation in the Carbon Footprint of Hemodialysis Treatment. Issue 9 (September 2022) - Sehgal, Ashwini R.; Slutzman, Jonathan E.; Huml, Anne M.
Significance Statement: Studies have demonstrated that hemodialysis facilities have a high environmental effect because the treatment requires large amounts of energy, water, and supplies. However, data regarding how much greenhouse gas emissions from hemodialysis treatment vary across facilities, treatments, and emission contributors have been lacking. In this study, the authors estimated magnitude and sources of variation in the carbon footprint of hemodialysis treatment. They found that the annual emissions per hemodialysis facility are equivalent to emissions from the annual energy use of 93 homes, and emissions per treatment are equivalent to driving an average automobile for 238 km (149 miles). Carbon footprints across facilities, treatments, and emission contributors also varied substantially. Understanding the magnitude and variation in greenhouse gas emissions may help identify measures to reduce the environmental effect of hemodialysis treatment. Visual Abstract: Abstract : Background: Greenhouse gas emissions from hemodialysis treatment in the United States have not been quantified. In addition, no previous studies have examined how much emissions vary across facilities, treatments, and emission contributors. Methods: To estimate the magnitude and sources of variation in the carbon footprint of hemodialysis treatment, we estimated life-cycle greenhouse gas emissions in carbon dioxide equivalents (CO2 -eq) associated with 209, 481 hemodialysis treatments in 2020 at 15 Ohio hemodialysis facilities belonging to the same organization. We considered emissions from electricity, natural gas, water, and supply use; patient and staff travel distance; and biohazard and landfill waste. Results: Annual emissions per facility averaged 769, 374 kg CO2 -eq (95% CI, 709, 388 to 848, 180 kg CO2 -eq). The three largest contributors to total emissions were patient and staff transportation (28.3%), electricity (27.4%), and natural gas (15.2%). Emissions per treatment were 58.9 kg CO2 -eq, with a three-fold variation across facilities. The contributors with the largest variation in emissions per treatment were transportation, natural gas, and water (coefficients of variation, 62.5%, 42.4%, and 37.7%, respectively). The annual emissions per hemodialysis facility are equivalent to emissions from the annual energy use in 93 homes; emissions per treatment are equivalent to driving an average automobile for 238 km (149 miles). Conclusions: Similar medical treatments provided in a single geographic region by facilities that are part of the same organization may be expected to have small variations in the determinants of greenhouse gas emissions. However, we found substantial variation in carbon footprints across facilities, treatments, and emission contributors. Understanding the magnitude and variation in greenhouse gas emissions may help identify measures to reduce the environmental effect of hemodialysis treatment.